2019
DOI: 10.1177/1759720x19877994
|View full text |Cite
|
Sign up to set email alerts
|

Update on the safety and efficacy of teriparatide in the treatment of osteoporosis

Abstract: Following the completion of the Fracture Prevention Trial, teriparatide was approved by the United States Food and Drug Administration and the European Medicine Agency as the first therapeutic anabolic agent for the treatment of postmenopausal women with severe osteoporosis. It subsequently received additional approval for the treatment of osteoporosis in men, and for the treatment of osteoporosis associated with glucocorticoid therapy in men and women at risk of fracture. In this review, we summarize the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 66 publications
1
32
0
2
Order By: Relevance
“…Other common side effects include nausea, arthralgia, fatigue, headache, and hypertension [32,33]. A previous study reported that these side effects usually start in the early treatment period and rarely occur after 3 months of treatment [17]. This report is consistent with the results of the present study in which side effects occurred in the early treatment period and were relieved with conservative treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other common side effects include nausea, arthralgia, fatigue, headache, and hypertension [32,33]. A previous study reported that these side effects usually start in the early treatment period and rarely occur after 3 months of treatment [17]. This report is consistent with the results of the present study in which side effects occurred in the early treatment period and were relieved with conservative treatment.…”
Section: Discussionsupporting
confidence: 92%
“…PTH is a bone forming agent that signi cantly reduces the risk of osteoporotic vertebral fracture and treats it effectively, especially in multiple level fractures [6,15,16]. While previous studies reported that conversion to anti-resorptive agents is necessary after 2 years of PTH administration for the treatment of osteoporosis, there is no standard duration of PTH administration established for acute osteoporotic vertebral fractures [17][18][19]. This study compared the conservative treatment group (Group C) and the intervention treatment group (Group I).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatment of osteoporosis is currently mainly aimed at osteoclasts ( Ensrud and Crandall, 2017 ; Roux and Briot, 2018 ), and the new therapy with teriparatide has shown a more curative effect in osteoporosis ( Minisola et al, 2019 ), which suggests that treatment options directed at osteoblasts are of great significance. Adenoviruses containing lncRNAs were used to treat mice and showed a significant therapeutic effect in many diseases, including ischemic myocardial injury ( Cai et al, 2019 ) and cardiac regeneration ( Ponnusamy et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…After 18 months of treatment, TPTD results in a larger increase in spinal BMD and improved microstructure compared with Risedronate [ 41 ]. In many countries TPTD has not been approved for use for men and hence observational data is correspondingly limited [ 42 ]. In the large registry studies (JFOS, exFOS), approximately 10% of patients were men (see Table 1 ) and the number was generally too small to allow sub-analysis of fracture data.…”
Section: Teriparatide Data In Various Patient Groupsmentioning
confidence: 99%